Self-Employment Trends Among First Nations, Métis, and Inuit (2001–2021) - Brooks, Tasha (Journal of Aboriginal Economic Development, 2025)
This article explores self-employment trends among Indigenous Peoples in Canada between 2001 and 2021, focusing on 2016 onward. Using disaggregated data (i.e., data separated by First Nations, Métis, and Inuit identity) from Statistics Canada’s Census of Population, it examines changes in both self-employment rates and absolute numbers, revealing distinct patterns across Indigenous groups. The analysis finds that while Métis individuals consistently report the highest self-employment rates, First Nations, despite notable growth, continue to face structural barriers, particularly those imposed by the Indian Act. Inuit remain significantly underrepresented in self-employment. The article also draws attention to the underutilization of external business assistance: in 2017, 88% of self-employed First Nations, 72% of self-employed Inuit, and 91% of self-employed Métis reported receiving no outside support. These findings underscore the importance of disaggregated data and call for targeted funding models that reflect the diverse conditions shaping Indigenous self-employment in Canada.